Ultraviolet Autofluorescence Microscopy of Nanotyrannus lancensis Sections Reveals Blood Clots in Vessel Canals. (November 2022) - Armitage, Mark H.
Abstract : Abstract: Theropod dinosaurs have captured the imagination of the public and paleontologists alike. Histology of the bones of theropods has revealed much about dinosaur physiology, behavior, and growth. Histology and ultraviolet fluorescence (UVFL) microscopy of one controversial dinosaur, Nanotyrannus lancensis, reveals the presence of blood clots in post-fixed vessel canals of claw, vertebra, and other isolated post-cranial elements collected at Hell Creek, MT. These clots are thicker, more closely adherent to canal walls, and more reactive to 347 nm UVFL incident light than unfixed specimens. Theropod histology images in the literature display similar clots, and those should be subjected to UVFL for confirmation. In addition, nematodes are evidently preserved in vessel canals of dinosaurs.